Evaluation of the tumorigenic potential of vermiculite by intrapleural injection in rats. Issue 2 (April 1973) - Hunter, B.; Thomson, C.
Abstract : Hunter, B., and Thomson, C. (1973). British Journal of Industrial Medicine, 30, 167-173. Evaluation of the tumorigenic potential of vermiculite by intrapleural injection in rats. Vermiculite, the geological name for a group of hydrated laminar minerals, has industrial application in areas previously restricted to the use of asbestos. In this assessment of its tumorigenicity, Rhodesian chrysotile asbestos or vermiculite was injected into the pleural cavity of rats. Mesotheliomata developed in 48% of the rats treated with asbestos. No tumours occurred which were associated with the vermiculite injections.